DESIGNING A PARCEL-BASED QUERY SYSTEM FOR RESERVOIR WATERSHEDS OF ISTANBUL, TURKEY - Ogurlu, Mustafa; Bayram, Bulent (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
Istanbul is one of the most crowded metropolitan areas of the world with an approximate population of 13 million. Fresh water is supplied to this megacity from seven reservoirs located on both the European and the Asian sides. Thus, protection of water resources is extremely important. Due to increase in water demand and to protect the existing water resources from pollution, it is necessary to hinder and almost stop any human activities such as construction works at the watersheds of these reservoirs. In this study, a web-based GIS system has been designed which allows to make queries by the property owners to get basic information about the status of their parcel. This system is designed to support the works of Istanbul Water and Sewerage Administration (ISKI). Using this system, the usage or construction-right and more spatial information of the parcels which are located in the protection zones of the reservoirs can be queried easily. The first version of the developed system has been activated by ISKI in 2008 and the last version has been completed in 2010. The developed web-based system has been visited by nearly 159,000 people and around 500,000 parcels were queried. In the year of 2011 this number has been doubled.
Keywords: reservoir; protection zones; web-based GIS; Environmental Sciences & Ecology